Percutaneous vascular closure device of the femoral access site after coronary interventions for acute coronary syndrome -immediate and short term follow-up - Manzil, Ashraf Safiya; Vala, Sidharaj; Vala, Sidharaj (International Journal of Research in Medical Sciences, 2017)
Background: Around 7 million patients undergo percutaneous interventional vascular procedures worldwide annually and this number is expected to escalate further in coming years. The aim of this study was to analyse immediate and short term follow up of patients with acute coronary syndrome (ACS) who had undergone percutaneous coronary intervention (PCI) through femoral route and closure with vascular closure device. Methods: This was non randomised, single centre study and was conducted in a tertiary care institution between January 2013 to June 2014 with 62 ACS patients undergoing femoral access invasive cardiac interventional procedure. Perclose A-T system was used in all patients as closure device. Patients were followed up to 15 days of clinical evaluation. Results: Of 62 ACS patients, 40 (64.5%) were with non-ST elevation myocardial infarction and 22 (35.5%) patients had history of unstable angina. The perclose device achieved closure within 5 to 10 minutes and all patients were kept in hospital stay for 2 to 3 days. There was one major complication of continuous bleeding, one incidence of small pseudo aneurysm, and two incidences of small hematomas with need of blood transfusion. Conclusions: This study demonstrates the ability of arterial closure device to safely and effectively achieve arterial closure in patients undergoing percutaneous intervention for ACS.